2018
DOI: 10.4103/ams.ams_150_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of attachment and proliferation of human gingival fibroblasts on different collagen membranes

Abstract: Background and Aim:Human gingival fibroblasts cultured on collagen membrane as an alternative treatment method used in tissue regeneration can lead to improved results in root coverage. The aim of this study was to evaluate the human gingival fibroblast proliferation and adhesion cultured on three types of collagen membranes.Materials and Methods:In this in vitro study, first-line human gingival fibroblast cells (HGF1-RT1) prepared and cultured on three membranes, including porcine pericardium (PP) (Jason, Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The limited number of flat polyhedral cells with long cytoplasmic extensions attached to the membrane surfaces may have been caused by the short incubation duration, which was 3 days in this experiment; another reason may be that cells were lost in the process of preparation and fixation. Similar results were observed in another experiment that involved a crosslinked membrane [35]. The AlamarBlue viability assay was used to assess the viability and proliferation of the cultured cells on the collagen membranes using a migration assay assembly.…”
Section: Discussionsupporting
confidence: 68%
“…The limited number of flat polyhedral cells with long cytoplasmic extensions attached to the membrane surfaces may have been caused by the short incubation duration, which was 3 days in this experiment; another reason may be that cells were lost in the process of preparation and fixation. Similar results were observed in another experiment that involved a crosslinked membrane [35]. The AlamarBlue viability assay was used to assess the viability and proliferation of the cultured cells on the collagen membranes using a migration assay assembly.…”
Section: Discussionsupporting
confidence: 68%
“…Despite this, there were numerous other studies that employed even more complex collagen matrices than a simple coating, confirming the positive effect of this structural protein on the growth, vitality, and migration of fibroblasts [ 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 96%
“…A scaffold that is suitable for biomedical applications must be highly porous, interconnected, and have a fibrous structure that supports biological processes, including cell growth, migration, and differentiation [ 16 ]. Previous in-vitro studies [ 10 , 26 ] demonstrated that fibroblast cells are able to adhere to collagen membrane for seven days; hence, the membrane needs to be intact and remain stable within the same duration after the surgical procedure to allow the establishment of the periodontal ligament cell attachment and proliferation [ 18 ]. This study demonstrated that there are significant changes in AM microstructures after 28 days of hydrolytic degradation test.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study by Ardakani et al found that the viability of fibroblast cells cultured on the cross-linking membrane reduced after seven days of observation when compared with native collagen membranes [ 26 ]. It can be assumed that the cross-linking of collagen membranes may somewhat affect cell attachment despite increasing the membrane degradation time.…”
Section: Discussionmentioning
confidence: 99%